KEPERCAYAAN MASYARAKAT TERHADAP TEMPAT KERAMAT DI DESA SILAU MARAJA KECAMATAN SETIA JANJI KABUPATEN ASAHAN - Lubis, Kholila Rahma; Ritonga, Sakti; Ismail, Ismail (CV. Kalimasada Group, 2023)
Indonesian people still believe in places that they consider to have supernatural powers. In certain communities, such as the village of Silau Maraja, there are certain places and spaces that are considered by the community to have a special position, which is called the community of sacred places. The Silau Maraja community has carried out various ways to protect the sacred place where there is an irrigation dam in the belief that it will provide safety and peace to the community, which is called the